Mayors à La Mancha: An Aspect of Depression Leadership in Canadian Cities - Taylor, John (Urban History Review / Revue d'histoire urbaine, 1981)
Conventional city politics — that is, non-partisan politics loosely identified with Liberal and Conservative urban elites — dominated major Canadian cities to the late nineteenth or early twentieth centuries. At that time they were challenged by representatives of a broader democracy in the form of Socialist organizations and Charismatic individuals with personal followings. With few exceptions the challenges were unsuccessful. The crisis of the 'thirties, however, proved more amenable to both types of challengers. The Charismatics of the depression proved once again to be ephemeral, unable to establish a permanent hold on their cities. But they often altered patterns sufficiently, if temporarily, either to enable Convention to beat back a Socialist challenge or to enable the Socialists to succeed to control.